A consciência que vem do tambor: uma leitura freiriana sobre a pedagogia afrocarnavalesca de Salvador - Silva, José Walter Silva e (2022)
Starting from the premise that all social formation, expressed in the culture of social groups, nations, and native peoples, among others, develop pedagogies aligned with their readings and worldviews, this thesis investigated the pedagogy underlying the conceptions and practices of the afoxés and the afros (groups) from Salvador. To do so, the following question was raised as a central problem: if in every cultural phenomenon an educational dimension is structured, tacitly or explicitly, and if the ontological vocation of the oppressed classes is liberation, as Paulo Freire exposes, the sociocultural practices of these groups. Do afrocarnavalesques include an anti-racist pedagogy? As a result of a set of socioeconomic, political, and cultural factors that conditioned their formations, such Afro-Carnaval entities became known not only as playful expressions, but also as possibilities for the Afro-Bahian population, but not exclusively for them, to be able to transform the world from their own words. It was considering such observations and seeking to answer the central question of this investigation, that the following hypothesis was formulated: at the same time that the intensive use of slave labor in the economic formation of Salvador deepened the dehumanizing character of its civilizing process, constituting in the post- abolition of a racist structure, the reaction to racism triggered the construction of a reading of the world that feeds and is fed by Afoxés and Afro groups through praxis aimed at raising awareness of the Afro-Bahian people, thus constituting an anti-racist pedagogy. Making use of an imaginary character that, among other aspects, problematizes this sociocultural phenomenon, suggests theoretical approaches and presents important aspects of the research universe (the carnival of Salvador and its afoxés and the Afro groups), the investigation is conducted from the dialectical method in the perspective of historical materialism. The investigation references its sources in the bibliographical research and in the field research, in addition to using, as the main data collection technique, the in-depth semi-structured interview, carried out with representative leaders of the Afoxés and Afro groups; composers; representatives of black collectives; representative of the Salvador Municipal Carnival Council, revelers, as well as an intellectual linked to Brazilian black culture and thought (Zulu Araújo). Based on Paulo Freire's theoretical contributions, it takes from this author, as main analytical categories, oppression, loveliness, humanization, culture, awareness, hope, utopia, wordworld, in addition to the concepts of education and pedagogy. Alongside Freire, other theoretical references used were Jacob Gorender, Clóvis Moura, Sílvio Almeida, José Ramos Tinhorão; Maria Isaura Pereira de Queiroz, José Eustáquio Romão, Jason Mafra and Afonso Celso Scocuglia. By situating pedagogy as a reading of the world aimed at transforming society through education, the research showed that, in the historical-social context of Salvador, examined here, an Afro-Carnaval pedagogy of a critical, decolonial and counter-hegemonic nature is developed, originating from the carnival and community practices of the afoxés and the afro blocks. Such a movement, by developing different processes of conscientization, creates, at the same time, possibilities for a cultural dialogue with schools and the educational system without compromising its main characteristic, that of being an unschooled pedagogy aimed at denouncing racism and advertising of actions capable of facing it, with a view to overcoming this form of oppression.